PREHARVEST SPROUTING RESISTANCE IN SPRING BREAD WHEAT CARRYING CHROMOSOME 6Agi(6D) FROM Agropyron intermedium - V. A. Krupnov; G. Yu. Antonov; A. E. Druzhin; O. V. Krupnova (Вавиловский журнал генетики и селекции)
A significant adverse effect of chromosome 6Agi(6D)-from Agropyron intermedium on preharvest sprouting resistance was foundin inbredlines (F7–F10 or senior) andnear-isogeniclines of red-grain andwhite-grain common spring wheat. The red-grain recombinant inbredlines, carrying this substitution chromosome, varied significantly in this trait, probably, owing to the genetic background effect. The causes of the adverse effect of chromosome 6Agi(6D) from Agropyron intermedium on preharvest sprouting resistance are unknown.